Standard test method for expansion (pin test) of copper and copper-alloy pipe and tubing
This test method establishes the requirements for the expansion pin test for copper and copper-alloy pipe and tubing with an inside diameter of 0.125 in. (3.2 mm) and greater or an outside diameter up to and including 4 in. (102 mm).